Effect of the pig rearing system on the final volatile profile of Iberian dry-cured ham as detected by PTR-ToF-MS - Sánchez del Pulgar, J; Soukoulis, C; Carrapiso, A I; Cappellin, L; Granitto, P; Aprea, E; Romano, A; Gasperi, F; Biasioli, F (Meat Science, 2013)
The volatile compound proﬁle of dry-cured Iberian ham lean and subcutaneous fat from pigs fattened outdoors on acorn and pasture (Montanera) or on high-oleic concentrated feed (Campo) was investigated by proton transfer reaction time-of-ﬂight mass spectrometry. In addition to the usual proton transfer ionization the novel switchable reagent ions system was implemented which allows the use of different precursor ions (H3O+ , NO+ and O2 + ). The analysis of the lean and subcutaneous fat volatile compounds allowed a good sample discrimination according to the diet. Differences were evident for several classes of compounds: in particular, Montanera hams showed higher concentrations of aldehydes and ketones and lower concentrations of sulfur-containing compounds compared to Campo hams. The use of NO+ as precursor ion conﬁrmed the results obtained with H3O+ in terms of classiﬁcation capability and provides additional analytical insights.
Keywords: aldehydes; Aldehydes: analysis; Animal Feed; Animal Husbandry; Animal Husbandry: methods; Animals; diet; Dietary Fats; Dietary Fats: analysis; Dietary Fats: pharmacology; Dry cured ham; Ions; Ketones; Ketones: analysis; Mass spectrometry; Mass Spectrometry: methods; meat; Meat: analysis; Nuts; Oleic Acid; Oleic Acid: pharmacology; Poaceae; Proton transfer reaction mass spectrometry; Quercus; Rearing system; subcutaneous fat; Subcutaneous Fat: metabolism; Sulfur Compounds; Sulfur Compounds: analysis; Swine; Switchable reagent ions; Time of flight; Volatile Organic Compounds; Volatile Organic Compounds: analysis

Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I.; Tomás-Barberán, Francisco a (Journal of Agricultural and Food Chemistry, 2007)
Ellagitannin-containing foods (strawberries, walnuts, pomegranate, raspberries, oak-aged wine, etc.) have attracted attention due to their cancer chemopreventive, cardioprotective, and antioxidant effects. Ellagitannins (ETs) are not absorbed as such but are metabolized by the intestinal flora to yield urolithins (hydroxydibenzopyran-6-one derivatives). In this study, Iberian pig is used as a model to clarify human ET metabolism. Pigs were fed either cereal fodder or acorns, a rich source of ETs. Plasma, urine, bile, lumen and intestinal tissues (jejunum and colon), feces, liver, kidney, heart, brain, lung, muscle, and subcutaneous fat tissue were analyzed. The results demonstrate that acorn ETs release ellagic acid (EA) in the jejunum, then the intestinal flora metabolizes EA sequentially to yield tetrahydroxy- (urolithin D), trihydroxy- (urolithin C), dihydroxy- (urolithin A), and monohydroxy- (urolithin B) dibenzopyran-6-one metabolites, which were absorbed preferentially when their lipophilicity increased. Thirty-one ET-derived metabolites were detected, including 25 urolithin and 6 EA derivatives. Twenty-six extensively conjugated metabolites were detected in bile, glucuronides and methyl glucuronides of EA and particularly urolithin A, C, and D derivatives, confirming a very active enterohepatic circulation. Urolithins A and B as well as dimethyl-EA-glucuronide were detected in peripheral plasma. The presence of EA metabolites in bile and in urine and its absence in intestinal tissues suggested its absorption in the stomach. Urolithin A was the only metabolite detected in feces and together with its glucuronide was the most abundant metabolite in urine. No metabolites accumulated in any organ analyzed. The whole metabolism of ETs is shown for the first time, confirming previous studies in humans and explaining the long persistency of urolithin metabolites in the body mediated by an active enterohepatic circulation.
From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)The following values have no corresponding Zotero field: publisher: American Chemical Society accession-num: 17990850
Keywords: Animal; Animals; bile; bioavailability; Biological Availability; Body Fluids; Body Fluids: chemistry; Cereals; Cereals: chemistry; colon; diet; ellagic acid; Ellagitannin; gall bladder; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: metabolism; Hydrolyzable Tannins: pharmacokinetics; intestine; metabolism; Models; Quercus; Seeds; Seeds: chemistry; Swine; Swine: metabolism; Tissue Distribution; urolithin

Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco a (Journal of Agricultural and Food Chemistry, 2007)
Ellagitannin-containing foods (strawberries, walnuts, pomegranate, raspberries, oak-aged wine, etc.) have attracted attention due to their cancer chemopreventive, cardioprotective, and antioxidant effects. Ellagitannins (ETs) are not absorbed as such but are metabolized by the intestinal flora to yield urolithins (hydroxydibenzopyran-6-one derivatives). In this study, Iberian pig is used as a model to clarify human ET metabolism. Pigs were fed either cereal fodder or acorns, a rich source of ETs. Plasma, urine, bile, lumen and intestinal tissues (jejunum and colon), feces, liver, kidney, heart, brain, lung, muscle, and subcutaneous fat tissue were analyzed. The results demonstrate that acorn ETs release ellagic acid (EA) in the jejunum, then the intestinal flora metabolizes EA sequentially to yield tetrahydroxy- (urolithin D), trihydroxy- (urolithin C), dihydroxy- (urolithin A), and monohydroxy- (urolithin B) dibenzopyran-6-one metabolites, which were absorbed preferentially when their lipophilicity increased. Thirty-one ET-derived metabolites were detected, including 25 urolithin and 6 EA derivatives. Twenty-six extensively conjugated metabolites were detected in bile, glucuronides and methyl glucuronides of EA and particularly urolithin A, C, and D derivatives, confirming a very active enterohepatic circulation. Urolithins A and B as well as dimethyl-EA-glucuronide were detected in peripheral plasma. The presence of EA metabolites in bile and in urine and its absence in intestinal tissues suggested its absorption in the stomach. Urolithin A was the only metabolite detected in feces and together with its glucuronide was the most abundant metabolite in urine. No metabolites accumulated in any organ analyzed. The whole metabolism of ETs is shown for the first time, confirming previous studies in humans and explaining the long persistency of urolithin metabolites in the body mediated by an active enterohepatic circulation.
From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)
Keywords: Animal; Animals; bile; bioavailability; Biological Availability; Body Fluids; Body Fluids: chemistry; Cereals; Cereals: chemistry; colon; diet; ellagic acid; Ellagitannin; gall bladder; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: metabolism; Hydrolyzable Tannins: pharmacokinetics; intestine; metabolism; Models; Quercus; Seeds; Seeds: chemistry; Swine; Swine: metabolism; Tissue Distribution; urolithin

A survey of helminth infection in Eurasian badgers (Meles meles) in relation to their foraging behaviour in a Mediterranean environment in southwest Portugal - Rosalino, Luís Miguel; Torres, Jordi; Santos-Reis, Margarida (European Journal of Wildlife Research, 2006)
This study provides the first data on the helminth fauna of the Eurasian badger in the southwestern edge of its range (Grândola Mountain, Portugal) and interprets the results in relation to badger diet and feeding behaviour. By examination of 163 badger faecal samples, faecal developmental stages (eliminative forms) of four helminth species and one genus were identified: one cestode (Atriotaenia incisa) and four nematodes (Mastophorus muris, Molineus patens, Uncinaria criniformis and Strongyloides sp.). The overall prevalence of parasites was 62%, with limited seasonal variation. Single parasite excretions were dominant and Strongyloides sp. excretion was the most common. Diet assessment based on 450 faecal samples revealed that badgers consumed mainly insects and fruits. No correlation was detected between helminth prevalence and diet. Apparently, diet (mainly insects) and feeding behaviour (fossorial), together with the species’ social behaviour (anal scent marking of group members), facilitate the infection with helminths. The helminth fauna of Eurasian badgers in Grândola Mountain has isolationist characteristics, apparently indicating low host colonisation.
Keywords: cork oak woodlands; diet; endoparasites; helminths; meles meles; Portugal

WINTER DIET OF RED DEER STAG (CERVUS-ELAPHUS L) AND ITS RELATIONSHIP TO MORPHOLOGY AND HABITAT IN CENTRAL SPAIN - ALVAREZ, G; MARTINEZ, T; MARTINEZ, E (FOLIA ZOOLOGICA, 1991)
The winter diet of red deer stags in a mediterranean environment of Central Spain is studied. Tree foliage and shrubs made up 95.5% of the diet, particularly Quercus rotundifolia (35.4%). Arbutus unedo (19.7%), Rosmarinus officinalis (9.4%), Phillyrea angustifolia (7%), Erica spp. and Cistus ladanifer. Herbaceous species formed 4% of the diet, mainly in a dry condition. There was a high similarity between the diets in the two periods studied, December and the end of January, with greater diversity in December. In January, the dominance of Quercus rotundifolia and Arbutus unedo increased. A relationship was detected of diet with body weight and antler growth. The largest animals consumed Arbutus unedo heavily, indicating a preference for forest understories with dense developed shrubs in mountain areas, while the smaller individuals associated with Erica umbellata, Phillyrea angustifolia and herbaceous species, had a wider diet niche and occupied less sheltered zones.
APS
Keywords: diet; Mediterranean; red deer; Spain